The Continuous Categorization of Space through Binary Oppositions in Uzbek and English Folklore Onomastics - Matyakubov, Xakimboy Khamidjanovich (The Lingua Spectrum, 2026)
This article explores the categorization of the concept of space in Uzbek and English folklore onomastics through the framework of binary oppositions. The study provides a comparative analysis of the semantic, cognitive, and linguocultural characteristics of spatial names occurring in folklore texts. Particular attention is devoted to oppositions such as “self-other,” “sacred-ordinary,” “center-periphery,” “earth-sky,” and “near-far,” which reflect the worldview, mythological thinking, and cultural memory of the people. The research demonstrates that spatial onyms in folklore are closely connected with historical experience, national values, and ethnocultural perceptions. The article identifies both common typological features and national-cultural peculiarities in the representation of space within Uzbek and English folklore traditions. Special emphasis is placed on the analysis of sacred spaces, border territories, and images of unknown or dangerous places that carry symbolic meanings in folk consciousness. Through the study of spatial representations, the article reveals how folklore preserves collective cultural knowledge and reflects traditional systems of values. The findings contribute to a deeper understanding of the onomastic landscape of spatial concepts in folklore texts and provide important theoretical and practical insights for comparative folklore studies, cognitive linguistics, ethnolinguistics, and linguocultural research. Along with this, the role of theonyms in the formation of new words within a particular ethnos was examined.